Pelatihan dan Pengelolaan Udang Rebon Menjadi Snack Sumpia di Desa Pulau Kampai Kec. Pangkalan Susu Kab. Langkat - Zaifatur Ridha; Hayatun Sabariah; Lia Ariska Ritonga (Mujtama': Jurnal Pengabdian Masyarakat, 2023)
Shrimp are a fairly high source of animal protein. Rebon Shrimp IS a species of shrimp that lives in the sea and is commonly used as fish food due to its consistent size and economic value. In the Kampai Island region, many fishermen sell raw unprocessed rebon at the beginning of the rebon season because the price is also quite cheap. In fact, quite a few bamboo shoots have been left alone to rot. Also, the processing of rebon shrimp in the Kampai Island area is still simple, namely, easy to dry and only process into shrimp paste. That's why this nonprofit aims to introduce the processing of rebon shrimp into processed food products like sumpia. The strategy employed in this activity was field observation, namely, conducting observations around the village community of Kampai Island related to the management of rebon shrimp. Then the socialization of this mentoring activity targeted PKK mothers and high school students in terms of training and rebon processing. From the results of the socialization of processed rebon, it was found that rebon shrimp can not only be processed into shrimp paste, but also be a convenient sumpia snack as a family snack and used as an upcoming home fried in the growing family -shrimp and rolled with spring roll skin, it has a savory taste, aroma, texture, appearance and color very delicious to be enjoyed in peace with the family.